Transition Zone1 Negatively Regulates Arabidopsis Aluminum Resistance Through Interaction With Aconitases - Liu, Jiajia; Shi, Benhui; Zhang, Mengxin; Liu, Guangchao; Ding, Zhaojun; Tian, Huiyu (Frontiers in Plant Science, 2022)
The soluble form of aluminum (Al) is a major constraint to crop production in acidic soils. The Al exclusion correlated with the Al-induced organic acid is considered as an important mechanism of Al resistance. The regulation of organic acid exudation in response to Al stress mediated by the root organic acid transporters has been extensively studied. However, how plants respond to Al stress through the regulation of organic acid homeostasis is not well understood. In this study, we identified the functionally unknown transition zone1 (TZ1) as an Al-inducible gene in the root transition zone, the most sensitive region to Al stress, in Arabidopsis. tz1 mutants showed enhanced Al resistance and displayed greatly reduced root growth inhibition. Furthermore, TZ1 was found to interact with the aconitases (ACOs) which can catalyze the conversion from citrate, one of the most important organic acids, into isocitrate. Consistently, in tz1 mutants, the citric acid content was highly increased. Collectively, this study provides evidence to show that TZ1 negatively regulates root growth response to Al stress through interacting with ACOs and regulating citric acid homeostasis.